Optimization of daytime fuel consumption for a hybrid diesel and photovoltaic industrial micro-grid - Dufrane, Stacey, author; Marchese, Anthony, advisor; Zimmerle, Daniel, advisor; Suryanarayanan, Siddharth, committee member; Bradley, Thomas, committee member (Colorado State University. Libraries, 2017)
The work to be presented will examine the optimization of daytime diesel fuel consumption for a hybrid diesel and photovoltaic (PV) industrial micro-grid with no energy storage. The micro-grid utilizes a control system developed to forecast PV transients and manage the diesel generators providing electrical supply to the micro-grid. The work focuses on optimization of daytime fuel consumption when PV generation is available. Simulations were utilized to minimize diesel consumption while maintaining secure operations by controlling both PV curtailment and diesel generation. The control system utilizes a cloud forecast system based upon sky imaging, developed by CSIRO (Australia), to predict the presence of cloud cover in concentric "rings" around the sun's position in the sky. The control system utilizes these cloud detections to establish supervisory settings for PV and diesel generation. Work included methods to optimize control response for the number of rings around the sun, studied the use of two different sizes of generators to allow for increased PV utilization, and modification of generator controller settings to reduce fault occurrence. The work indicates that increasing the number of rings used to create the PV forecast has the greatest impact on reducing the number of faults, while having a minimal impact on the total diesel consumption. Additionally, increasing the total number of generators in the system increases PV utilization and decreases fuel consumption.
Keywords: micro-grid; microgrid; photovoltaic